2013
DOI: 10.1016/j.fertnstert.2013.01.153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal chronic disease on obstetric complications in twin pregnancies in a United States cohort

Abstract: Objective To evaluate the effect of maternal chronic disease on obstetric complications among twin pregnancies. Design Multicenter retrospective observational study. Setting The 12 Consortium on Safe Labor (CSL) clinical centers (19 hospitals). Patient(s) Twin pregnancies (n=4,821) delivered ≥ 23 weeks of gestation and classified by maternal chronic disease (either none or any of the following: asthma, depression, hypertension, diabetes, and heart, thyroid, gastrointestinal or renal disease). Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…(21) However this study did not demonstrate any apparent increase in adverse birth outcomes associated with prelabor CD; indeed, the neonatal outcomes tended to favour prelabor CD.…”
Section: Discussioncontrasting
confidence: 60%
“…(21) However this study did not demonstrate any apparent increase in adverse birth outcomes associated with prelabor CD; indeed, the neonatal outcomes tended to favour prelabor CD.…”
Section: Discussioncontrasting
confidence: 60%
“…Early preterm births are less frequent than late (34–36 weeks), as Vogel et al reported in the WHO Global Survey, with 11.9% of preterm birth below 34 completed weeks [ 6 ]. Higher early preterm rates are important, as they are associated with higher neonatal morbidity and perinatal death rates, mainly due to respiratory complications [ 6 , 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal death has been described as up to four times higher in twin pregnancies than in singletons, mainly due to preterm birth, fetal growth restriction, low Apgar scores and extremely low birth weight [ 5 , 6 , 23 , 25 ]. In our study, it was found to be 2.5 times higher for the first twin and 3.5 for the second one.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chronic disease prior to pregnancy has been associated with an increased risk for hemorrhage in twin gestations [44]. The metabolic changes that occur during pregnancy, including relative hyperglycemia, hyperlipidemia, and disturbance of coagulation, represent a transient excursion into the metabolic syndrome [45].…”
Section: Discussionmentioning
confidence: 99%
“…ART national surveillance summaries are limited to birth outcomes reported by the patient herself or her obstetric provider [54][55][56]. Prior studies [44,45] have relied on linkages between ART cycles and vital records using only maternal and infant dates of birth or probabilistic algorithms [56]. Although there is a high degree of comparability between the SART CORS and vital records [27], our study design assures more accurate linkage between ART treatment cycles, vital records, and the hospital discharge birth data and a more complete picture of perinatal outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 99%